The equation that represents Jacob's age is x = y + z + 2
From the question, the following information was provided :
Jacob's age is two years more than the sum of the ages of his siblings Becky and Micah.
This above information can be represented with the equation below
Jacob = 2 + ( Becky + Micah) (equation 1)
If :
x represents Jacob's age
y represents Micah's age
z represents Becky's age
Equation 1, can be rewritten as x = y + z + 2
Micah's age can be determined by making Micah the subject of the formula in the above equation
Micah = Jacob - Becky - 2 (equation 2)
If :
x represents Micah's age
y represents Becky's age
z represents Jacob's age
Micah's age can be rewritten as :
x = z - y - 2
Becky's age age can be determined by making Becky the subject of the formula in the first equation.
Becky = Jacob - Micah - 2 (equation 3)
If:
x represents Becky's age
y represents Jacob's age
z represents Micah's age
Equation 3 can be rewritten as :
x = y - z - 2
Check here for a related question : brainly.com/question/21843246?referrer=searchResults
Using a system of equations, it is found that the correct equation is given by:
, which is option B.
---------------
Which is given by option B.
A similar problem is given at brainly.com/question/24233433
Answer: No
Explanation: In the first problem, 2 is a base and 7 is an exponent.
The 7 that is raised up means we multiply our base together seven times.
This means the same thing as 2 × 2 × 2 × 2 × 2 × 2 × 2 × 2 or 128.
On the other hand, 2 × 7 is 14.
It can also be thought of as 2 + 2 + 2 + 2 + 2 + 2 + 2 or 14.
Answer:
No, 2^7 is not the same thing as 2 x 7
Step-by-step explanation:
When you are doing 2 x 7 you multiply 7 by 2. For 2^7, you multiply 2 by 2 7 times.
2 x 7 = 2 x 7
2^7 = 2 x 2 x 2 x 2 x 2 x 2 x 2
Answer: You divide both sides by -3.
Step-by-step explanation:
We're asked to solve the equation: .
To do this, divide both sides by -3:
Simplify
Therefore, that's our answer.
Answer:
divide both sides by - 3
Step-by-step explanation:
given the equation
- 3y = 2x - 7
to isolate y then divide both sides by - 3
y = , that is
y =
or
y = x + = - x +